Navigating sources of teacher uncertainty: exploring teachers' collaborative discourse when learning a new instructional approach. Issue 1 (2nd January 2023) - Starrett, Emily; Firetto, Carla M.; Jordan, Michelle E.
ABSTRACT: As educators learn about new tools to utilise in their classrooms, there can be questions and ambiguity that accompany the new information; yet they are not always given time or support to address their questions. Acknowledging and embracing the uncertainties that teachers inevitably face when learning about new instructional approaches can help push them to explore new possibilities and better support student learning. Taking a qualitative discourse analytic approach, we used a single-group case study design to explore how a group of STEM teachers navigate uncertainty when learning a new instructional approach throughout two collaborative discourse sessions within the context of a professional learning space. Grounding our study in a social constructivist lens, we interpreted and compared the sources of uncertainty that teachers expressed. We then mapped out the flow of the conversations to explore how teachers navigated those sources through the trajectory of their collaborative discourse. Analysis revealed that teachers expressed uncertainties while offering suggestions in the form of pedagogical techniques in response to others' uncertainties, often leading to shifts, resolutions, and generations of new uncertainty expressions. We suggest that professional learning spaces offer an opportunity for teachers to collaboratively navigate their uncertainties when learning new instructional approaches.